Factors Determining a Choice of a Math Competition as a Form of Educating Gifted Children: a Case Studio of Professor Matulionis ‘Young Mathematicians’ Competition - Dabrišienė, Vilija; Visockienė, Ona (Pedagogika, 2015)
The aim of this article is to reveal factors determining a choice of a Math competition as a form of educating gifted children, on the basis of a case of professor Matulionis ‘young mathematicians’ competition. Research showed that a pupil’s decision to participate in a Math competition is determined by the following groups of factors: 1. Impact of education policy is not very significant, however, due to it, a number of participants of competitions has increased and teachers began using various teaching forms while educating gifted children. 2. A pupil’s decision is more influenced by his / her personal, inner factors than by the external ones. Pupil‘s sex is a very important factor: boys tend to participate in competitions more often and their results are better. Even though they rarely attend extra lessons, they have a desire to win. 3. One of the major factors is a location and a school a pupil came from. A particular school, and in some cases not even a school but a location (Kretinga or Visaginas), influences a number of participants as well as their results. 4. Another important factor is the groups of peers sharing the same interests. Pupils who belong to such groups not only more often strive to achieve better results but also more frequently discuss their work with their friends and teachers and enjoy solving problems.